2016
DOI: 10.5455/aim.2016.24.61-65
|View full text |Cite
|
Sign up to set email alerts
|

ELISA Test for Analyzing of Incidence of Type 1 Diabetes Autoantibodies (GAD and IA2) in Children and Adolescents

Abstract: Introduction: Anti GAD (antibodies on glutamic acid decarboxylase) and anti-IA2 antibodies (against tyrosine phosphatase ), today, have their place and importance in diagnosis and prognosis of Type 1 diabetes. Huge number of patients with diabetes mellitus type 1 have these antibodies. Insulin antibodies are of critical importance in diagnosis of diabetes mellitus type 1 for pediatric population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 22 publications
1
8
0
Order By: Relevance
“…Indeed, type 1A diabetes is an autoimmune disease due to the destruction of pancreatic islet β-cells by T cells. These results corroborate those of Delic-Sarac et al [10], who found anti-GAD and anti-IA2 autoantibodies in the diabetic patient's serum. The presence of these autoantibodies in siblings of T1D shows that they constitute a population at risk for diabetes, as Siljander et al [12], De Grijse et al [13] and Simonen-Tikka et al [20], showed in their study.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Indeed, type 1A diabetes is an autoimmune disease due to the destruction of pancreatic islet β-cells by T cells. These results corroborate those of Delic-Sarac et al [10], who found anti-GAD and anti-IA2 autoantibodies in the diabetic patient's serum. The presence of these autoantibodies in siblings of T1D shows that they constitute a population at risk for diabetes, as Siljander et al [12], De Grijse et al [13] and Simonen-Tikka et al [20], showed in their study.…”
Section: Discussionsupporting
confidence: 92%
“…It is an incurable disease that is gaining momentum in Africa and particularly in Côte d'Ivoire. Today, the diagnosis of type 1A diabetes is biological (fasting glucose greater than 1.26 g / l) and requires the search for autoantibodies of diabetes as a confirmation marker for autoimmune process [8][9][10]. According to several authors, these autoantibodies of diabetes are present in siblings of type 1A diabetics (T1D) and are markers of the imminence of diabetes in this population at risk [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…With regard to anti-IA2 autoantibodies, the results showed a maximum value of 310 IU/ml in the first year of diabetes, followed by a brutal fall from the 2nd year, 5th, 6th until the 7th year (248.60 ± 95.40 IU/ml, 89.80 ± 25.78 IU/ml, 49.95 ± 39.05 IU/ml and 25.73 IU/ml). These results show that β-cells of Langerhans islets of the endocrine pancreas of these T1D know undergo a fast destruction, which can lead 7 to the death of these. The rebound of anti-GAD autoantibodies observed at the 7th year of diabetes and at the 9th year for anti-IA2 is thought to be due to the persistence of the humoral immune response against the islet cells of the Langherans of the pancreas.…”
Section: Discussionmentioning
confidence: 69%
“…It is an incurable disease that is gaining momentum in Africa and particularly in Côte d'Ivoire. Today, the diagnosis of type 1A diabetes is biological (fasting glucose greater than 1.26 g / l) and requires the search for autoantibodies of diabetes as a confirmation marker for autoimmune process [7]. According to some authors, these autoantibodies diabetes disappear with the duration of diabetes [8].…”
Section: Introductionmentioning
confidence: 99%
“…For the control group, to rule out the diagnosis of T1D, we conducted a GAD 65 assay. GAD 65 assay was conducted by using an indirect enzyme-linked immunoabsorbent assay (ELISA) method, as previously described by literature [22]. Nutritional status was defined by plotting body mass index (BMI) into a standardized WHO chart for children aged 10-19 years old, then categorized as obese, overweight, normal, and underweight.…”
Section: Methodsmentioning
confidence: 99%